IMPROVING THE EFFICIENCY OF EXPENDITURE FOR FINANCIAL SUPPORT COMPREHENSIVE SERVICES - E. Elistratova (Модернизация, инновация, развитие)
The article presents the author developed proposals to improve the financial mechanism of the federal budget spending on fi nancial support services in the field of general education. The approaches to the budgetary allocations for the provision of educational services in accordance with the results of the activities of agencies and their providers in a competitive resource allocation.The aim of the article is to solve scientific and practical task of improving the effi ciency of budget spending on general education.Tasks article. Identify ways of improving the fi nancial mechanism of the Russian Federation budget spending on general education and to develop a set of measures for their implementation.Results. The author suggests an approach to planning and budgetary allocations based on performance monitoring results and the eff ectiveness of budget expenditures: The allocation of grants for other purposes from the Russian Federation budget, in addition to grants for fi nancial support for the implementation of the state (municipal) task for the provision of educational services by educational institutions, demonstrating the positive dynamics of performance; The inclusion of indicators of quality in the calculation of the funding of the state (municipal) task for the provision of educational services.